Angiotensin II‐induced cardiac hypertrophy and fibrosis are promoted in mice lacking Fgf16. (18th April 2013) - Matsumoto, Emi; Sasaki, Sayaka; Kinoshita, Hideyuki; Kito, Takuya; Ohta, Hiroya; Konishi, Morichika; Kuwahara, Koichiro; Nakao, Kazuwa; Itoh, Nobuyuki
<x xml:space="preserve">Abstract</x> Fibroblast growth factors (Fgfs) are pleiotropic proteins involved in development, repair and metabolism. Fgf16 is predominantly expressed in the heart. However, as the heart function is essentially normal in Fgf16 knockout mice, its role has remained unclear. To elucidate the pathophysiological role of Fgf16 in the heart, we examined angiotensin II‐induced cardiac hypertrophy and fibrosis in Fgf16 knockout mice. Angiotensin II‐induced cardiac hypertrophy and fibrosis were significantly promoted by enhancing Tgf‐β1 expression in Fgf16 knockout mice. Unexpectedly, the response to cardiac remodeling was apparently opposite to that in Fgf2 knockout mice. These results indicate that Fgf16 probably prevents cardiac remodeling, although Fgf2 promotes it. Cardiac Fgf16 expression was induced after the induction of Fgf2 expression by angiotensin II. In cultured cardiomyocytes, Fgf16 expression was promoted by Fgf2. In addition, Fgf16 antagonized Fgf2‐induced Tgf‐β1 expression in cultured cardiomyocytes and noncardiomyocytes. These results suggest a possible mechanism whereby Fgf16 prevents angiotensin II‐induced cardiac hypertrophy and fibrosis by antagonizing Fgf2. The present findings should provide new insights into the roles of Fgf signaling in cardiac remodeling.